TECHNICAL AND FINANCIAL RESULTS OF OBTAINING ELECTRICITY FROM MICRO HYDROPOWER PLANTS - Abdurauf, Abdulaziz Uulu; Xusniddinovich, Suvonov Jaxongir; Shavkatjonovich, Ahmadjonov Sayyodbek (PT. Antis International Publisher, 2025)
Objective: This study aims to analyze the efficiency and feasibility of micro-hydroelectric power plants in various geographical locations. It explores the fundamental principles of hydropower generation, emphasizing the potential of micro-hydro systems to provide sustainable electricity, particularly in remote areas. The research also evaluates the impact of different construction methods and turbine types on overall energy output and efficiency. Methods: The study employs a combination of theoretical analysis and practical calculations to determine the efficiency and feasibility of micro-hydro systems. The fundamental equation for power generation (P = 9.81 * Q * H * η) is applied to different scenarios. Various micro-hydro construction methods, including diversion and simple in-stream systems, are compared. Additionally, the performance of active and reactive hydroturbines is assessed, along with power regulation techniques such as frequency and voltage adjustment mechanisms. Results: Micro-hydropower plants demonstrate high efficiency, reaching up to 75-80%, significantly outperforming thermal power plants. The power output varies based on water flow rate, pressure head, and turbine efficiency. Proper site selection, considering factors like river slope and seasonal water stability, enhances performance. A case study calculation reveals that a micro-hydropower system with a flow rate of 3 m³/s and a head of 1.5 m can generate approximately 73.7 kW, enough to power several households. However, challenges such as seasonal fluctuations, construction costs, and environmental concerns, including ecosystem disruption, must be addressed. Novelty: This study provides a comprehensive comparison of different micro-hydro construction techniques and turbine types, offering practical insights for optimizing efficiency and sustainability. It highlights the importance of selecting appropriate locations and materials to maximize energy output while minimizing environmental impact. Additionally, the research explores innovative frequency and voltage regulation methods, which are crucial for maintaining stable energy supply in micro-hydro applications.